Growth curve of dairy artificial insemination bulls raised under Thai tropical conditions - Sarakul, Mattaneeya; Koonawootrittriron, Skorn; Elzo, Mauricio A.; Suwanasopee, Thanathip (Agriculture and Natural Resources, 2019)
The growth curve of dairy artificial insemination bulls was evaluated under Thai tropical conditions. Data consisted of 4,963 monthly body weights from 140 bulls collected from 1996 to 2015 at the Semen Production and Dairy Genetic Evaluation Center of the Dairy Farming Promotion Organization of Thailand. Four breed groups were defined based on their Holstein (H) fraction: BG1 (0.96 ≤ H ≤ 1.00), BG2 (0.91 ≤ H < 0.96), BG3 (0.86 ≤ H < 0.91) and BG4 (0.44 ≤ H < 0.86). Linear (Quadratic) and nonlinear (Gompertz, Logistic, Von Bertalanffy and Brody) models were compared for goodness of fit using -2logL, Akaike information criterion (AIC), corrected AIC (AICC) and Bayesian information criterion (BIC). The Quadratic model had lowest values for these four criteria. Predicted weights at ages 30 mo and 60 mo were higher for bulls in BG2 than bulls in BG1, BG3 and BG4. Growth curves from these bulls would be useful to identify sires expected to produce steers with faster growth rates and heifers with younger ages at first calving. Unfortunately, weights from steer and heifer progeny from these bulls were unavailable. Consequently, progeny weights would need to be collected if genomic selection for growth traits were to be implemented in the Thai multibreed population.